Development of a Network DEA Model to Measure Production Line's Performance: a Case Study for Automation and Labor Combination - Nik Afieza, Che Azhar; Ahmad Rasdan, Ismail; Muhammad Ariffin, Mansor (2014)
Nowadays, growth of industry can be seen as a nature of the world. Each company race again each other to increase productivity to produce new, high quality and product that fulfill customer demand. One can achieve the Key Performance Indicator (KPI) or targeted goal but without considering the cost, manpower, time or others elements is inefficient toward productivity. In this paper, we studied the effectiveness of production line that equipped with automation to determine whether the return of investment for automation is worth compare to output obtained. We apply Data Envelopment Analysis (DEA) to measure efficiencies of production line where DEA is one of excellent tool that can evaluate efficiencies and have been use widely in many sectors.